2012
DOI: 10.3892/or.2012.1941
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and reduction of MMP gene expression in the U373 cell line by polyphenolics in Aronia melanocarpa and by curcumin

Abstract: Malignant brain tumours are rare but are the most challenging types of cancers to treat. Despite conventional multimodality approaches available for their management, the outlook for most patients remains dismal due to the ability of the tumour cells to invade the normal brain. Attention has now focused on novel therapeutic interventions such as as the use of micronutrients. Both chokeberry extract (Aronia melanocarpa), which is rich in natural pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 38 publications
0
26
2
Order By: Relevance
“…Although they are emerging as regulators of nervous system development and adult brain functions, their role in cell death remains to be elucidated [40,41]. Our in vitro data, however, show an increased expression of Mmp16 and Adam1a and the decrease of Adamts2 during CGNs rescue [15].…”
Section: Enzymes Involved In Extracellular Matrix Remodelingcontrasting
confidence: 46%
“…Although they are emerging as regulators of nervous system development and adult brain functions, their role in cell death remains to be elucidated [40,41]. Our in vitro data, however, show an increased expression of Mmp16 and Adam1a and the decrease of Adamts2 during CGNs rescue [15].…”
Section: Enzymes Involved In Extracellular Matrix Remodelingcontrasting
confidence: 46%
“…Data has shown that curcumin is able to suppress expression of MMP-1, MMP-3, MMP-9, and MMP-14 in GBM cell lines U87MG and U373MG via the common upstream AP-1 and MAP kinases [22, 23, 54]. Urokinase-type plasminogen activator (uPA) is a serine protease that starts a degradative cascade by converting extracellular plasminogen to plasmin and eventually degrades extracellular matrix collagen and activates other MMPs to aid in invasion [55].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…Glioma cell lines and culture conditions. U251, U373 and T98G cells (39)(40)(41) were cultured in humidified atmosphere of 5% CO 2 /air in RPMI-1640 medium (Life Technologies, Monza, Italy) supplemented with 10% fetal bovine serum (FBS, Celbio, Milan, Italy), 100 U/ml penicillin and 100 mg/ml streptomycin. To verify the effect on proliferation, cell growth was monitored by determining the cell number/ml using a Z2 Coulter Counter (Coulter Electronics, Hialeah, FL, USA).…”
Section: Synthesis and Characterization Of Pnas The Synthesis And Chmentioning
confidence: 99%